In Vivo Imaging of Hypoxia-Inducible Factor Regulation in a Subcutaneous and Orthotopic GL261 Glioma Tumor Model Using a Reporter Gene Assay - Sandra Bürgi; Aline Seuwen; Ruth Keist; Johannes vom Berg; Joanes Grandjean; Markus Rudin (Molecular Imaging)
Intratumoral hypoxia changes the metabolism of gliomas, leading to a more aggressive phenotype with increased resistance to radio- and chemotherapy. Hypoxia triggers a signaling cascade with hypoxia-inducible factor (HIF) as a key regulator. We monitored activation of the HIF pathway longitudinally in murine glioma tumors. GL261 cells, stably transfected with a luciferase reporter driven under the control of a promoter comprising the HIF target gene motive hypoxia response element, were implanted either subcutaneously or orthotopically. In vivo experiments were carried out using bioluminescence imaging. Tumors were subsequently analyzed using immunofluorescence staining for hypoxia, endothelial cells, tumor perfusion, and glucose transporter expression. Transient upregulation of the HIF signaling was observed in both subcutaneous and orthotopic gliomas. Immunofluorescence staining confirmed hypoxic regions in subcutaneous and, to a lesser extent, intracranial tumors. Subcutaneous tumors showed substantial necrosis, which might contribute to the decreased bioluminescence output observed toward the end of the experiment. Orthotopic tumors were less hypoxic than subcutaneous ones and did not develop extensive necrotic areas. Although this may be the result of the overall smaller size of orthotopic tumors, it might also reflect differences in the local environment, such as the better intrinsic vascularization of brain tissue compared to the subcutaneous tissue compartment.